ASUHAN KEPERAWATAN Ny. A CHRONIC KIDNEY DISEASE MELALUI FOOT MASSAGE UNTUK MENURUNKAN FATIGUE - Puti Widya Gravinta; Dedy Siska (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Chronic Kidney Disease (CKD) is a global health problem characterized by increasing incidence, prevalence, morbidity, and mortality. CKD is defined as kidney damage with a decrease in Glomerular Filtration Rate (GFR) to less than 60 ml/min/1.73 m² for more than three months. This study aimed to provide nursing care to a patient with CKD through the application of foot massage therapy to reduce fatigue levels in the Hemodialysis Unit of Harapan Bunda Hospital, Batam. The method used was a case study based on the nursing care process, including assessment using the FACIT Fatigue Scale, which initially showed a score of 11 (severe fatigue). The nursing diagnosis was fatigue related to chronic physiological conditions and long-term treatment. Interventions were carried out through four sessions of foot massage therapy. The evaluation showed a reduction in fatigue levels, with the score increasing from 16 (severe fatigue) on the first day to 32 (not fatigued) on the fourth day. The patient also reported improved energy, strength, ability to perform daily activities, reduced tiredness, and better appetite. In conclusion, foot massage therapy can be effective in reducing fatigue levels in CKD patients undergoing hemodialysis and may improve their quality of life.Keywords: Fatigue, foot massage, chronic kidney disease, hemodialysis, nursing implementation.